Can Waqf be a Solution to Answer The Challenges of Globalization? - Khoirul Umam; Syamsuri Syamsuri; Moch Imron Isro'i (Ijtimā iyya Journal of Muslim Society Research, 2021)
This study aims to analyze the opportunities of waqf in facing the challenges of globalization such as economic challenges that affect the level of inequality and high poverty, the challenges of education globalization that affect secondary school dropout rates. and the challenges of environmental globalization that affect the exploitation of land conversion. industry to the point of causing environmental damage. The results of this study indicate that waqf can be a solution in responding to the challenges of economic globalization by using waqf for social security programs, or a profitable investment for poverty eradication programs. And the solution to the globalization of education is to use waqf funds to support the operations of educational institutions, as well as provide facilities and scholarships for students so that they can continue to experience education without being burdened with costs. And finally, the solution in responding to the challenges of globalization is to make the status of land as a waqf so that it is not easily converted into industrial land that causes climate damage.